Breast milk feeding and cognitive ability at 7–8 years. Issue 1 (1st January 2001) - Horwood, L J; Darlow, B A; Mogridge, N
Abstract : OBJECTIVE: To examine the association between duration of breast milk feeding and cognitive ability at 7–8 years in a birth cohort of very low birthweight infants. DESIGN: 280 survivors from a national birth cohort of 413 New Zealand very low birthweight infants born in 1986 were assessed at age 7–8 years on measures of verbal and performance intelligence quotient (IQ) using the WISC-R. At the same time mothers were questioned as to whether they had elected to provide expressed breast milk at birth and the total duration of breast milk feeding. RESULTS: Some 73% of mothers provided expressed breast milk and 37% breast fed for four months or longer. Increasing duration of breast milk feeding was associated with increases in both verbal IQ (p < 0.001) and performance IQ (p < 0.05): children breast fed for eight months or longer had mean (SD) verbal IQ scores that were 10.2 (0.56) points higher and performance IQ scores that were 6.2 (0.35) points higher than children who did not receive breast milk. These differences were substantially reduced after control for selection factors associated with receipt of breast milk. Nevertheless, even after control for confounding, there remained a significant (p < 0.05) association between duration of breast milk feeding and verbal IQ: children breast fed for eight months or longer had adjusted mean (SD) verbal IQ scores that were 6 (0.36) points higher than the scores of those who did not receive breast milk. CONCLUSIONS: These findings add to a growing body of evidence to suggest that breast milk feeding may have small long term benefits for child cognitive development.